2020
DOI: 10.1051/0004-6361/201936709
|View full text |Cite
|
Sign up to set email alerts
|

NELIOTA: Methods, statistics, and results for meteoroids impacting the Moon

Abstract: Context. This paper contains the results from the first 30 months of the NELIOTA project for impacts of Near-Earth Objects/meteoroids on the lunar surface. Our analysis on the statistics concerning the efficiency of the campaign and the parameters of the projectiles and the impacts is presented. Aims. The parameters of the lunar impact flashes based on simultaneous observations in two wavelength bands are used to estimate the distributions of the masses, sizes and frequency of the impactors. These statistics c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
0
18
0
2
Order By: Relevance
“…Early observations, focused on maximising the impact detection rate, were preferentially carried out during meteor showers. These were followed by surveys where observations took place regularly under favourable lunar observing conditions, showing that the occurence of flashes is indeed correlated with showers (Suggs et al 2014;Liakos et al 2020). After the impact of a kg-sized meteoroid near the lunar terminator two dust clouds with typical expansion velocities of 0.1 and 3 km s −1 were observed (Berezhnoy et al 2019).…”
Section: Meteoroid Streams At the Moonmentioning
confidence: 95%
“…Early observations, focused on maximising the impact detection rate, were preferentially carried out during meteor showers. These were followed by surveys where observations took place regularly under favourable lunar observing conditions, showing that the occurence of flashes is indeed correlated with showers (Suggs et al 2014;Liakos et al 2020). After the impact of a kg-sized meteoroid near the lunar terminator two dust clouds with typical expansion velocities of 0.1 and 3 km s −1 were observed (Berezhnoy et al 2019).…”
Section: Meteoroid Streams At the Moonmentioning
confidence: 95%
“…A.5), duration and the calibrated peak magnitudes in R and I bands. Unfortunately, as it is derived by Xilouris et al (2018) and Liakos et al (2020), the reported magnitudes and errors on the NELIOTA database are approximate, while some selenographic coordinates are possibly reported incorrectly (swapped longitude and latitude).…”
Section: Neliotamentioning
confidence: 95%
“…In this work, for the flashes with numbers 1-80 we use the published magnitudes and selenographic coordinates (Xilouris et al, 2018;Liakos et al, 2020), while for the rest (81-112) we use the data as reported on the website. As we will see later, we use our method and re-compute the selenographic coordinates (Tab.…”
Section: Neliotamentioning
confidence: 99%
See 1 more Smart Citation
“…Video monitoring for flashes initially took place about 25 years ago (e.g., [6]), and they were first observed in the 1999 Leonids activity [7][8][9]. Lately, observations for flash detection have been conducted systematically [10][11][12].…”
Section: Introductionmentioning
confidence: 99%